2017
DOI: 10.3389/fnins.2017.00254
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70/Hsp90 Chaperone Machinery in Neurodegenerative Diseases

Abstract: The accumulation of misfolded proteins in the human brain is one of the critical features of many neurodegenerative diseases, including Alzheimer's disease (AD). Assembles of beta-amyloid (Aβ) peptide—either soluble (oligomers) or insoluble (plaques) and of tau protein, which form neurofibrillary tangles, are the major hallmarks of AD. Chaperones and co-chaperones regulate protein folding and client maturation, but they also target misfolded or aggregated proteins for refolding or for degradation, mostly by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
232
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(240 citation statements)
references
References 295 publications
(403 reference statements)
7
232
0
1
Order By: Relevance
“…Even variations of Hsp70 appear to be correlated with regulatory cell growth and differentiation processes following neurodegenerative states [38]. Indeed, an upregulation of Hsp70 detected in stressed hamsters fed with genistein tends to further underlie its protective measures in a similar fashion to that of other anti-apoptotic plus antidepressant compounds [39], and this is in line with its upregulatory trend reported during traumatic brain injuries [40] and during ischemic episodes [33].…”
Section: Discussionmentioning
confidence: 72%
“…Even variations of Hsp70 appear to be correlated with regulatory cell growth and differentiation processes following neurodegenerative states [38]. Indeed, an upregulation of Hsp70 detected in stressed hamsters fed with genistein tends to further underlie its protective measures in a similar fashion to that of other anti-apoptotic plus antidepressant compounds [39], and this is in line with its upregulatory trend reported during traumatic brain injuries [40] and during ischemic episodes [33].…”
Section: Discussionmentioning
confidence: 72%
“…The HSP family plays a major role in activating against protein misfolding in diseases including PD [21]. As reviewed by Lackie et al, early observation of Hsp90, Hsp70, Hsp60, Hsp40, and Hsp27 has provided a deeper insight into these chaperones [21]. For instance, Hsp60 was found to intervene in PD pathogenesis in 6-OHDA-lesioned rat models [22].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hsp60 was found to intervene in PD pathogenesis in 6-OHDA-lesioned rat models [22]. Hsp70 overexpression was reported to prevent α-synuclein accumulation and to reverse dopaminergic neuron loss [21]. Falsone et al revealed that Hsp90 blocked α-synuclein aggregation in an in vitro model [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HSP90 could regulate the proliferative and senescent client proteins [14], including PI3K, AKT, MAPKs, CDK4, Cyclin D1, and VEGF, which also indicated that HSP90 played an important role in the PD [24,25,38,39]. Quantitative proteomics technique is a reliable and precise method to predict the disease-specific targets and underlying mechanism [21].…”
Section: Discussionmentioning
confidence: 99%
“…S2 and Table S3). Previous studies have indicated that HSP90 plays an important role in the anti-PD field [22][23][24], therefore, HSP90AA1 and HSP90AB1 were speculated to be two critical proteins affected by URE treatment in MPP + -induced SH-SY5Y cells. HSP90, as a molecular chaperone, played an indispensable role in normal cellular homeostasis by regulating the folding, stability, and function of its client proteins, some of which have effects in regulating signal transduction pathways.…”
Section: Confirmation Of Differentially Expressed Proteins By Westernmentioning
confidence: 99%